Innovative Research on the Daily Management of College Students from the Perspective of University Counselors - Li, Yang (Education Insights, 2026)
With the continuous deepening of higher education transformations and profound changes in the growth environments of college students, student management in universities currently faces unprecedented opportunities and complex challenges. Students in the new era are increasingly characterized by highly active thinking, distinct individual personalities, and diverse channels for accessing information. Consequently, traditional management approaches have become largely inadequate for meeting their comprehensive developmental needs and academic expectations. As the primary implementers of daily student management and ideological education, university counselors play a vital and irreplaceable role in maintaining campus stability, fostering positive student growth, and fulfilling the fundamental educational mission of cultivating virtue through comprehensive education. In direct response to the pressing demands of educational digital transformation and modernized university governance structures, innovative approaches are urgently required to update and optimize university counselors' daily management practices. Based on the practical realities of contemporary student management and thoroughly analyzing its broader academic significance, this paper systematically examines the current challenges faced by counselors in higher education institutions. Furthermore, it proposes a comprehensive work framework centered on conceptual innovation, systemic restructuring, methodological advancement, digital platform development, and professional team enhancement, while suggesting actionable optimization pathways. The study ultimately concludes that innovating daily student management practices significantly enhances the scientific rigor, standardization, and precision of administrative efforts. This provides robust, sustainable support for promoting students' holistic development and achieving high-quality, long-term university development in a rapidly evolving educational landscape.